(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The heterocyclic chemistry is never ending and ever-growing subject. Pyrazole, a heterocyclic molecule, which leading the pharmaceutical business due to their immense therapeutic activities. Due to the potential biological activities of the pyrazole compounds, more research work is being conducted on these molecules and which further leads to the large investment on pyrazoles followed by invention of new potential drugs. An array of pyrazole benzamides (8a-8s) were prepared by reacting pyrazole hydrazides with different aldehydes and among the synthesized molecules 8g and 8i was the lead molecules. Structures of 8a-8s were confirmed by 1H NMR, LC-MS and IR spectroscopy and its biological activities were studied by molecular docking study and study shows almost all molecules have the activity for rheumatoid arthritis disease.